PENGARUH PENERAPAN E-FILING DAN PERAN ACCOUNT REPRESENTATIVE TERHADAP PENCITRAAN OTORITAS PAJAK DAN KEPATUHAN WAJIB PAJAK - Kiswara, Danar; Jati, I Ketut (E-Jurnal Akuntansi; Vol 15 No 1 (2016), 2016)
In practice, the need for quality system of tax revenue sophisticated, effective and efficient to increase in line with developments in information technology. The aim of this study was to determine the effect of the application of e-Filing system and the role of account representative for imaging the tax authority and taxpayer compliance. The study was conducted in East Denpasar STO by taking a sample of 120 taxpayers, using the method of sampling nonprobability, particularly purposive sampling technique. Collecting data using interview and questionnaire. Data analysis techniques in this study using path analysis techniques. Based on the analysis found that (1) the implementation of the e-Filing system significantly influence the role of AR, (2) implementation of e-Filing system significantly influence the imaging of the tax authorities, (3) AR significantly influence the role of imaging tax authorities, (4) implementation of e-Filing system significantly influence taxpayer compliance, (5) imaging tax authorities significantly influence taxpayer compliance, (6) role AR significant impact on taxpayer compliance.
Keywords: application of e-Filing system, the role of AR, image of the tax authorities, tax compliance